Relationship of Quality Health Service Towards Loyalty of Patient at Bhayangkara Hospital Kendari - Andi Mauliyana; Nurul Aisyiah Rizal (MIRACLE Journal Of Public Health, 2021)
Based on the Profile of the Bhayangkara Kendari Hospital, the number of patient visits to the inpatient unit from 2017-2018 experienced an increase in the number of patient visits. The purpose of this study was to determine the relationship between the quality of health services and the loyalty of inpatients at the Bhayangkara Hospital, Kendari City. This study used a cross-sectional study design with a population of 358 people and a sample of 78 people who were determined by taking the sample using the accidental sampling method. Data analyze using chi square test. The results showed that there was relationship between physical evidence (X2count=4,197; φ=0,264), reliability (X2count=5,816; φ=0,305), and empathy (X2count=9,442; φ=0,378) with inpatient loyalty. The conclusion is there was a weak relationship between physical evidence, reliability, and empathy with inpatient loyalty at the Bhayangkara Hospital Kendari City. The hospital should pay more attention to the comfort of the patient's room and improve skills in serving patients so that it can improve the quality of service to patients and encourages patients to come back for treatment at Bhayangkara Hospital Kendari City.